SIRT1 Antagonizes Oxidative Stress in Diabetic Vascular Complication - Meng, Teng; Qin, Weifeng; Liu, Baohua (Frontiers in Endocrinology, 2020)
Diabetic mellitus (DM) is a significant public health concern worldwide with an increased incidence of morbidity and mortality, which is particularly due to the diabetic vascular complications. Several pivotal underlying mechanisms are associated with vascular complications, including hyperglycemia, mitochondrial dysfunction, inflammation, and most importantly, oxidative stress. Oxidative stress triggers defective angiogenesis, activates pro-inflammatory pathways and causes long-lasting epigenetic changes to facilitate the development of vascular complications. Therefore, therapeutic interventions targeting oxidative stress are promising to manage diabetic vascular complications. Sirtuin1 (SIRT1), a class III histone deacetylase belonging to the sirtuin family, plays critical roles in regulating metabolism and ageing-related pathological conditions, such as vascular diseases. Growing evidence has indicated that SIRT1 acts as a sensing regulator in response to oxidative stress and attenuates vascular dysfunction via cooperating with adenosine-monophosphate-activated protein kinase (AMPK) to activate antioxidant signals through various downstream effectors, including peroxisome proliferator-activated receptor-gamma co-activator 1 (PGC-1α), forkhead transcription factors (FOXOs) and peroxisome proliferative-activated receptor α (PPARα). In addition, SIRT1 interacts with hydrogen sulfide (H2S), regulates NADPH oxidase, Endothelial NO synthase and mechanistic target of rapamycin (mTOR) to suppress oxidative stress. Furthermore, mRNA expression of sirt1 is affected by microRNAs in DM. In the current review, we summarise recent advances illustrating the importance of SIRT1 in antagonizing oxidative stress. We also discuss whether modulation of SIRT1 can serve as a therapeutic strategy to treat diabetic vascular complications.